Four new species of the subfamily Psilodercinae (Araneae: Ochyroceratidae) from Southwest China - Wang, Chunxia; Li, Shuqiang (Zootaxa, 2013)
Four new species of the family Ochyroceratidae are described from Southwest China: Althepus christae sp. nov., Leclercera undulatus sp. nov., Psiloderces incomptus sp. nov. from Yunnan; and P. exilis sp. nov. from Guangxi. The four species belong to the subfamily Psilodercinae.